2017
DOI: 10.1038/nnano.2017.113
|View full text |Cite|
|
Sign up to set email alerts
|

Antigen-capturing nanoparticles improve the abscopal effect and cancer immunotherapy

Abstract: Immunotherapy holds tremendous promise for improving cancer treatment1. Administering radiotherapy with immunotherapy has been shown to improve immune responses and can elicit an “abscopal effect”2. Unfortunately, response rates for this strategy remain low3. Herein, we report an improved cancer immunotherapy approach that utilizes antigen-capturing nanoparticles (AC-NPs). We engineered several AC-NPs formulations and demonstrated that the set of protein antigens captured by each AC-NP formulation is dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
486
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 585 publications
(511 citation statements)
references
References 37 publications
3
486
1
Order By: Relevance
“…Studies have shown that during radiotherapy, additional administration of nanoparticles that can specifically absorb neoantigens can enhance the efficacy of antigen‐presenting cells (APCs) in antigen presentation, which further strengthens the abscopal effect and increases the growth inhibition of distal tumors 15. Similar to photodynamic therapy, which can enhance the outcome of checkpoint blockage therapy, a combination of photothermal therapy (PTT, another photo‐induced therapeutic manner) with immune stimulation mediated by carbon nanotubes can enhance the immune response with the subsequent administration of anti‐CTLA‐4 16, 17, 18, 19.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that during radiotherapy, additional administration of nanoparticles that can specifically absorb neoantigens can enhance the efficacy of antigen‐presenting cells (APCs) in antigen presentation, which further strengthens the abscopal effect and increases the growth inhibition of distal tumors 15. Similar to photodynamic therapy, which can enhance the outcome of checkpoint blockage therapy, a combination of photothermal therapy (PTT, another photo‐induced therapeutic manner) with immune stimulation mediated by carbon nanotubes can enhance the immune response with the subsequent administration of anti‐CTLA‐4 16, 17, 18, 19.…”
Section: Introductionmentioning
confidence: 99%
“…By optimizing the surface properties, they showed that these AC-NPs could deliver the released antigen to APCs and significantly improve the efficacy of anti-PD-1 treatment (Fig. 6) [148]. Currently, confirmed ICD chemo-inducers include oxaliplatin, doxorubicin, mitoxantrone, bortezomib, and cyclophosphamide [149].…”
Section: Application Of Nanomaterials For Cancer Vaccine Designmentioning
confidence: 99%
“…Recent examples are NP that enhance the function of antigen presenting cells leading to strong anti-tumour T cell cytotoxicity [112,113]. A number of biotechnology/pharmaceutical companies are pursuing NP-based vaccines [114].…”
Section: Nanotechnologies For Tissue Engineering and Wearables For Hementioning
confidence: 99%